GLOBALISASI DAN RESPON PENDIDIKAN AGAMA ISLAM DI SEKOLAH - A. Suradi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Islamic education is education that is not limited by the institutional environment of Islam or by the study of certain sciences, and based on purely Islamic experience. Yet it reaches all aspects of the knowledge, experience, and aspirations of the Muslim community. So the basic view that became the starting point of science PAI is the theoretical-practical aspects in all fields of science related to existing problems and that will exist in society. Problems in society continue to grow without stagnation. Therefore, PAI as an anticipative solution to prepare not only morally but the spirit of struggle to compete to develop science. Because modern times now want the dynamics of life to flow very swiftly.